Palmitoylethanolamide attenuates neurodevelopmental delay and early hippocampal damage following perinatal asphyxia in rats - Herrera, María Inés (2022)
Fil: Herrera, María Inés. Pontificia Universidad Católica Argentina. Facultad de Psicología. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina